IMPROVING SPECTRUM UTILISATION IN CR WITH MULTIPLE MODULATION SCHEMES THROUGH DL - Subhash Kulkarni , P Ravinder Kumar, Sandeep V M , (Design Engineering, 2021)
Spectrum sensing is an important criterion for improving spectrum utilisation in a cognitive radio network (CRN) with multiple modulation schemes. CRN is more powerful, at the same time, increases the complexity of sensing. This paper addresses the issues through Deep Learning (DL) based spectrum sensing. Presented here are three models with improving performance. The model is trained and verified on real-time data.